Conceptual model for funding of businesses based on Islamic principles in Malaysia - Dangulbi, Sani Musa (2012)
Islamic Banking Financial Institutions (IBFIs) were established in the 1970s in order to remedy the failure of the conventional financial institutions in providing a system of financing that is deemed equitable and just to society while meeting profit motives through risk sharing principle based on principles of Islam. The size and extent of Islamic banking and finance globally in the last three decades of existence is impressive and is a sign of its acceptability worldwide among the billions of world Muslim population as well as non-Muslim. However, arguments abound that the practices of Islamic banking and finance have deviated from being Shariah compliant especially regarding funding of projects and products like bay bithaman „ajil, BBA; the circumventing of interest through a backdoor charging of Riba. More fundamentally the Islamic Banking and Financial system uses fiat currency and operate the Fractional Reserve Banking system where money is created out of nothing through project financing and loan extension which result in illegitimate transfer of wealth from the poor to the rich which violates shariah principle. More so, Islamic financial institutions are said to be financing not funding thereby not meeting the maqasid al-shariah (Objectives of Islamic Law) and now leaning heavily on and rapidly converging with the conventional system. Against this backdrop, I embarked on this thesis as the platform to document my journey as a Muslim entrepreneur to search for funding that observes the principles of Islam, in particular meeting the objectives of Islamic law (maqasid al-shariah, MaS). I investigate why IBFIs are more inclined on financing than funding as well as exploring the circumstances leading to the claims that Islamic financial institutions are not meeting the objectives of the Shariah (maqasid al-shariah, MaS). In this research too, a conceptual model of funding of business that observes the fundamentals of maqasid al-shariah, (MaS) for the benefits of general society is proposed. The study employs qualitative and idiographic research approaches using interviews in addition to othersources from secondary data such as books, journals, documentaries and audio-visual materials as the means of data collection. The research also adopts the philosophical methodology of jurisprudence of analogy in Islam (mustasfa) of Imam Al-Ghazali which he used to simply the understanding of Islamic philosophy during his time and I believe such analogy is appropriate my thesis because it is about Islam, therefore I adopted the analogy to investigate the funding of business in Islam. The target respondents for the interview are the Shariah Advisory Councils, some experienced Shariah scholars, and academics teaching Islamic finance, the Islamic Bank Customers and the Islamic banks Officials in Malaysia. The study analyses and interprets the data collected through the principles of Grounded Theory where themes and concepts are classified into various thematic categories and further referenced against the fundamentals of Shariah from Quran, Sunnah and Ijmah. This approach of addressing the fundamental issue of funding of business in Islam in line with maqasid alshariah (MaS) is not common in most Islamic Financial research. The findings of this search journey from the documented works in the literature and the interview revealed several results. From the documented works in the literature, this search journey research found that IBFIs are more of debt financing than equity funding which raised different opinion among researchers; those that argue that such financing is in line with shariah because it does not involve Riba and those who argue that such financing is not in line with shariah because debt based financing meets only the ‗form‘ and not the ‗substance‘ of shariah. For the latter group of researchers, current financing is based on the principles of banking not fully n the principles of Islam because there is no risk sharing but rather risk shifting. Findings from the interview on the other hand revealed that in theory Islamic banking services are different from conventional banking services, however in practice both operate fractional reserve banking and use fiat currency to finance projects which makes no difference between the former and the latter. The journey also found that it is possible to get funding of business based on the principles of Islam without going through the banks since banking is about lending and lending is about debt creation which is usurious in nature. The journey confirm that the best alternative for funding of business based on principles of Islam apply Asset based trading (CAPEX); murabahah and Liquidity based trading (OPEX); Venture capital and fund management (mudharabah and musharakah) because there is equity and risk sharing based on partnership not based on customer banker relationship. Finally, the journey develops a conceptual framework for funding of business based on principles of Islam. The findings of this study contribute in various ways as they contribute to the current body of knowledge and stimulate future research. It has some practical implications as the findings help the policy makers and practitioners to revise current IBFIs policy and programmes in line with principles of Islam and maqasid al-shariah. The study helps the Muslim ummah to shape their thinking framework in arriving at judgments regarding the level of shariah compliance (Islamicity) of products offered by Islamic financial institutions. In conclusion, Muslims should rememberthat Allah says; And if Allah were to impose blame on the people for their wrongdoing, He would not have left upon the earth any creature, but He defers them for a specified term. And when their term has come, they will not remain behind an hour, nor will they precede [it]‘ (Q16:61).